Suboptimal fault tolerant control design with the use of discrete optimization - Kowalczuk, Zdzisław; Oliński, Krzysztof E. (Zielona Góra: Uniwersytet Zielonogórski)
This paper presents a concept of designing fault tolerant control systems with the use of suboptimal methods. We assume that a given (nonlinear) dynamical process is described in a state space. The method consists in searching (at the off-line stage) for a trajectory of operational points of the system state space. The sought trajectory can be constrained by certain conditions, which can express faults or failures already detected.
Keywords: optimal control; fault tolerant systems; nonlinear models; operations research; discrete optimization